Motnje hranjenja in požiranja pri otrocih z razcepi v orofacialnem področju - Jelenc, Nika (Zdravniški vestnik, 2019)
Background: Orofacial clefts are the most common congenital craniofacial malformations. Children with orofacial clefts do not only have problems with speech, but also with feeding and swallowing. Alternative methods of feeding need to be introduced in severe cases. Until now there has not been conducted a single study regarding feeding and swallowing problems in children with orofacial clefts in Slovenia. Methods: The aim of the study was to determine the prevalence and the type of feeding and swallowing problems in children with orofacial clefts, aged between five months and six years. An anonymous questionnaire for parents was created, containing questions about the type of the child's orofacial cleft, child's possible feeding, swallowing and speech problems, and special feeding gadgets. The questionnaire was initially tested in a pilot study during routine medical follow-up visits. Afterwards, it was sent to 93 parents of children with clefs, born in a period of three consecutive years. A descriptive statistics was used to present the prevalence of feeding and swallowing problems in children with orofacial clefts. The factors correlated with feeding problems were analysed. Results: Almost three-quarters of children had problems with feeding immediately after birth; problems with feeding later decreased, but they were still present in one quarter of all cases until the completed surgical treatment. Most difficulties occurred due to nasal regurgitation, excessive air intake while bottle feeding, and prolonged feeding time. Children with cleft palate with or without cleft lip had significantly more feeding problems in comparison to children with cleft lip only. Most parents used special feeding bottles and were generally satisfied with their use. More than a half of the parents believed that they had received too little information about feeding before and immediately after the child's birth. Conclusion: Despite the well-organized multidisciplinary care of children with orofacial clefts in Slovenia, parents still miss the professional counselling about feeding their children. Therefore, an additional education of nurses working in maternity hospitals will be necessary in the future. Considering the high prices of special feeding gadgets for children with orofacial clefts, covering of their costs by the health insurance would be welcome.
Keywords: dejavniki tveganja; feeding and swallowing problems; interventions; motnje hranjenja in požiranja; obravnava; orofacial clefts; questionnaire; razcepi v orofacialnem področju; risk factors; vprašalnik